Dividend Distribution and Stock Price of Nepalese Commercial Banks - Thapa, Bhim Kumar; Paudel, Ramesh Rasik; Chaulagain, Rajesh Kumar (Nexus: Journal of Interdisciplinary Engineering, Technology and Management, 2026)
This study investigates the impact of dividend payout ratio and dividend yield on the market price of shares (MPS) of Nepalese commercial banks. It aims to provide insights into how dividend practices and organizational scale influence market valuation in the Nepalese financial sector. A descriptive and explanatory research design was adopted under a quantitative approach with a positivist philosophy. The population comprised all 19 commercial banks listed on the Nepal Stock Exchange (NEPSE) over the ten years from 2015 to 2024. A census approach yielded 190 observations, of which 179 were retained after outlier diagnostics using standardized deleted residuals, Cook’s distance, and leverage values. Secondary data were collected from commercial banks’ annual reports and the NEPSE website. Data analysis was conducted using IBM SPSS Statistics, employing descriptive statistics, correlation, and multiple regression.The results show that the dividend payout ratio has a positive and significant effect on share price, consistent with dividend relevance theory. Conversely, dividend yield has a negative and significant impact, indicating that higher yields may signal weaker growth prospects. Firm size, measured by total assets, also negatively influences share price, suggesting a valuation discount for larger banks. Collectively, the predictors explain 49.5% of the variance in share price. The findings guide investors in assessing dividend distributions and managers in balancing shareholder returns with retained earnings. Policymakers should enhance transparency and efficiency to address valuation disparities among larger banks.This study contributes empirical evidence from Nepal, an emerging-market context, by combining dividend distribution and firm size to explain share price behavior.